Dynamic and Static Nature of Br4σ(4c–6e) and Se2Br5σ(7c–10e) in the Selenanthrene System and Related Species Elucidated by QTAIM Dual Functional Analysis with QC Calculations. (24th July 2020) - Hayashi, Satoko; Nishide, Taro; Nakanishi, Waro
Abstract : The nature of Br4 σ (4c–6e) of the B Br-∗- A Br-∗- A Br-∗- B Br form is elucidated for SeC12 H8 (Br)SeBr---Br-Br---Br Se(Br)C12 H8 Se, the selenanthrene system, and the models with QTAIM dual functional analysis (QTAIM-DFA). Asterisks (∗) are employed to emphasize the existence of bond critical points on the interactions in question. Data from the fully optimized structure correspond to the static nature of interactions. In our treatment, data from the perturbed structures, around the fully optimized structure, are employed for the analysis, in addition to those from the fully optimized one, which represent the dynamic nature of interactions. The A Br-∗- A Br and A Br-∗- B Br interactions are predicted to have the CT-TBP (trigonal bipyramidal adduct formation through charge transfer) nature and the typical hydrogen bond nature, respectively. The nature of Se2 Br5 σ (7c–10e) is also clarified typically, employing an anionic model of [Br-Se (C4 H4 Se)-Br---Br---Br-Se (C4 H4 Se)-Br ] −, the 1, 4-diselenin system, rather than (BrSeC12 H8 )Br---Se---Br -Br---Br-Se (C12 H8 Se)-Br, the selenanthrene system.